Exploring Wearable Devices for Enhanced Ergonomic Solutions: a Pharmaceutical Case Study - Carlos Albarrán Morillo; Micaela Demichela; John F. Suárez-Pérez; Nasli Yuceti Miranda Arandia; Mónica Andrea Camargo Salinas (Chemical Engineering Transactions)
The new paradigm descending from Industry 4.0, known as Industry 5.0, emphasizes the significance of human-centric factors and ergonomics in industrial processes. Creating an ergonomic workplace involves considering not only physical aspects but also cognitive, environmental and organizational factors. This holistic approach is vital for enhancing human productivity, satisfaction, and safety. In the Industry 4.0 landscape, the integration of ergonomics with advanced technologies provides comprehensive data for accurately assessing occupational hazards. This paper proposes an ergonomic assessment method employing a set of non-invasive wearable devices to monitor workers' activities and physiological metrics, complemented by subjective self-assessment questionnaires, during their shifts. This approach is implemented in a real-world setting within the pharmaceutical sector, where manual work involves repetitive motion tasks, making workers susceptible to musculoskeletal disorders and high stress levels. The findings demonstrate that implementing ergonomic evaluations can help the organization identify risks, ultimately enhancing operator well-being, safety, and productivity.